The radiative and hydrologic effects of a local switch from maize to Miscanthus - Roy, Gavin R., author; Vonder Haar, Thomas, advisor; Peters-Lidard, Christa, committee member; Niemann, Jeffrey, committee member; Denning, A. Scott, committee member (Colorado State University. Libraries, 2013)
Miscanthus (Miscanthus giganteus), a lush, dense grass that grows to be 3-4 meters tall, has been proven to be a substantially more productive biofuel crop than maize (Zea mays) due to its higher biomass output per unit area for conversion into ethanol. Moreover, Miscanthus is a perennial, biogeochemically sustainable crop, returning most of its nutrients to the soil each fall and needing less year-to-year maintenance than maize after its initial planting. Due to these potential benefits, a switch to Miscanthus as a viable biofuel alternative to maize has been suggested as a way to meet the current US energy goal of 30% displacement of domestic petroleum use by ethanol in the transportation sector by 2030, a goal that the existing US maize crop alone cannot achieve. Because maize and Miscanthus have significantly different vegetation characteristics, however, it is hypothesized that such a switch will lead to changes in the local surface radiation budget and hydrology. This study seeks to evaluate these changes. Perennial agriculture such as Miscanthus contributes to a greener surface earlier in the spring and later in the fall than maize (annual agriculture), subsequently leading to higher year-round albedo and water usage. Due to the denser growth of Miscanthus, evapotranspiration and thus absolute water usage are also higher than maize, especially during the summer. However, Miscanthus exhibits a deeper rooting depth than maize and therefore has access to deeper soil water. In this study, representative shifts in year-round albedo, green vegetation fraction, rooting depth, and leaf area index are parameterized and their combined radiative and hydrologic effects evaluated through uncoupled retrospective runs of a well-tested land surface model over an existing area of maize in the US Corn Belt. Sensitivity experiments are undertaken that likewise evaluate the individual contributions of each shifted parameterization scheme. It is found that the combination of these shifts leads to a yearlong average increase in latent heating of 12.16 W/m2 and a nearly commensurate decrease in average sensible heating of 12.67 W/m2 at the surface. It is also found that soil moisture availability plays a large role in the temporal persistence of these radiative effects, as modeled Miscanthus depletes the soil moisture in its rooting zone much more quickly, ending the growing season with an 11% decrease in volumetric soil moisture from maize. It is hypothesized that if soil moisture availability remains at a sustainable level, these effects will directly contribute to local cooling and moistening of the near-surface atmosphere.
Keywords: climate; hydrology; modification; radiation; switchgrass; Miscanthus